(untitled) (International Journal of Current Engineering and Technology, 2015)
Increased demands on the implementation of wireless sensor networks in automation of different applications in various fields including medicine, transportation, and precision agriculture results in relatively new wireless standards for improvement of the automation. Agricultural environment for various factors like soil moisture, temperature and humidity is very significant . This paper presents the use of zigbee wireless technology in automated irrigation management system which uses wireless sensor networks. Zigbee carries some advantages like being of low cost, low power and wireless mesh topology networking standard. Gsm/gprs or mobile phone can be used to access following information and service such as information and configuration pertaining to mobile device and sim card, sms services, data and voice link over mobile network. This paper provides us with a method to control the level of water supply to the crops which aims at high efficiency of water and electricity. This system utilizes sensors, zigbee modem, and gprs. The control is done automatically without any human interpositin by design, development and trial work of a monitoring system.